Applicability of Intelligent Electric Grid : Arctic Energy Project - Pietilä, Petri (Lapin ammattikorkeakoulu, 2017)
The purpose of the thesis was to do study Smart Grid solutions and apply the found technologies to answer to the following research problems: the enabling effect of Smart Grids on energy storage and production, exclusivity effect of using Smart Grid technologies, usage effect of the Smart Grid technology on customer level, Smart Grid solutions for a two-way power transfer, Smart Grid solutions for energy production control and load control possibilities and Smart Grid solutions and usage for safety margins and reserve margins. The thesis gives an insight into what it is meant by for example Smart Grid 1.0. The topics deals with the aspects of the distribution network and end-users of electricity. The security of the Smart Grid, distributed generation, electrical vehicles, and electricity storages are also presented. The thesis was carried out in collaboration with the Industry and Natural Resources RDI of Lapland University of Applied Sciences. The thesis was part of the Arctic Energy project’s work package 4.1 defined tasks for Lapland University of Applied Sciences. The work was written in English with the intention that people who work in the project are apart from Finland also from Sweden and Norway in which case English works as a common language. The thesis was executed as information retrieval and by applying the found information to the research problems. All the publicly available documents such as books, e-books and the literature in the field found on the internet was used as documentary material. The results of the thesis serves the targets of the work package and gave the needed information about the Smart Grid solutions to the people involved in the project. The aim set for the work was fulfilled and the results corresponds to the research problems. Opinnäytetyön tarkoituksena oli tutkia älyverkkoratkaisuja ja soveltaa löydettyjä teknologioita vastaamaan seuraaviin tutkimusongelmiin: älykkäiden sähköverkkojen mahdollistava vaikutus tuotantoon ja energian varastointiin, käytön mahdollinen ...